Intrinsic Radiosensitivity Is Not the Determining Factor in Treatment Response Differences between HPV Negative and HPV Positive Head and Neck Cancers - Paul Reid; Alexander H. Staudacher; Loredana G. Marcu; Ian Olver; Leyla Moghaddasi; Michael P. Brown; Yanrui Li; Eva Bezak (Cells, 2020)
Head and neck squamous cell carcinomas (HNSCC) resulting from human papillomavirus (HPV) are increasing in incidence but demonstrate significantly better treatment response than HNSCC from other causes such as tobacco and alcohol. This study sought to identify differences in HNSCC, intrinsic to HPV status, in their response to radiation dose. Previously unexamined changes in radio-responsiveness following fractionated X-ray irradiation were compared between HPV positive and negative statuses of HNSCC. Six HNSCC cell lines, 3 of each HPV status, were investigated for radiosensitivity by clonogenic assay and modelled by response as a function of dose. Generational cultures of each cell line were developed to follow changes in radiosensitivity after repeated irradiations simulating fractionated radiation therapy. As a group, the HPV positive cell lines were more radiosensitive, but with changes following repeated fractions of dose, and modelling of response as a function of dose, both statuses displayed large radiobiological heterogeneity. These findings challenge current radiobiological assumptions of head and neck cancers as early responding tissue to radiation and may go some way in explaining difficulties reaching consensus in stratification of treatment by HPV status. Consequently, results from this study do not support stratifying radiation therapy by HPV status.